50.3k views
1 vote
F−g+(−2)f, minus, g, plus, left parenthesis, minus, 2, right parenthesis where f = -3.005f=−3.005f, equals, minus, 3, point, 005 and g = 4.7g=4.7

User Asif Iqbal
by
5.9k points

2 Answers

4 votes

Answer:

the answer i got was

-9.705

Explanation:

i did it on khan

User Bernardo Meurer
by
5.4k points
1 vote

Answer:


f-g+(-2) = -9.705

Explanation:

Given


f = -3.005


g=4.7

Required

Determine
f-g+(-2)

We have:


f-g+(-2)

Open brackets


f-g+(-2) = f-g-2

Substitute values for f and g


f-g+(-2) = -3.005-4.7-2

Solve


f-g+(-2) = -9.705

User Afuc Func
by
5.9k points